2012
DOI: 10.1021/cg2007414
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Quality of Protein Crystals Grown in a High Magnetic Field Gradient

Abstract: Space-based microgravity environments have been utilized to obtain a highly ordered crystal because of the lack of gravity-induced convection. A superconducting magnet-based quasi-microgravity is also expected to contribute to the enhancement of the quality of protein crystals. We here report a case study on protein crystallization using fifteen kinds of samples in a magnetic field gradient, which was sufficient for magnetic levitation of water droplets. In three cases, rod-type crystals were aligned perpendic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…reduced under the magnetic condition (Figure 1c, d). A reduction in the number of crystal nuclei and a relatively slow crystal growth rate were observed in crystallization with static or gradient magnetic fields, as was a magnetic orientation of the crystals [5,9,18]. The observations of our crystallization experiment suggest that the crystal orientation, which is probably due to the magnetic fields, is the major effect on the crystallization of LH2.…”
Section: Data Collectionsupporting
confidence: 52%
See 1 more Smart Citation
“…reduced under the magnetic condition (Figure 1c, d). A reduction in the number of crystal nuclei and a relatively slow crystal growth rate were observed in crystallization with static or gradient magnetic fields, as was a magnetic orientation of the crystals [5,9,18]. The observations of our crystallization experiment suggest that the crystal orientation, which is probably due to the magnetic fields, is the major effect on the crystallization of LH2.…”
Section: Data Collectionsupporting
confidence: 52%
“…In gradient magnetic fields, diamagnetic waters and protein molecules receive a magnetic force and the upward magnetic force can suppress the natural convection due to gravity [8]. Therefore, crystallization under the gradient magnetic fields (magnetic force fields) provides additional favorable effects for protein crystals because the relatively slow supply rate of protein molecules could improve quality by decreasing the undesired impurity uptake during crystal growth [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, an interesting phenomenon was that protein crystals appeared to be highly oriented along the direction of the magnetic field (Yin et al, 2004;Ataka & Wakayama, 2002;Sato et al, 2000). Later, magnetic fields were found to be beneficial for the growth of high-quality protein crystals (Nakamura et al, 2012;Sazaki, 2009;Saijo et al, 2005;Sato et al, 2001;Lin et al, 2000). The mechanisms of the improvement in crystal quality have been discussed extensively in the past few years, and the major points include the following: (i) the damping of convection in both homogeneous and inhomogeneous magnetic fields, especially in a largegradient magnetic field (Leslie & Ramachandran, 2007;Wakayama, 2006;Qi et al, 2001;Sazaki et al, 1999), and (ii) an orientation effect arising from anisotropy in the magnetic susceptibility of crystals (Yin et al, 2004).…”
Section: Mechanisms For Effects On Crystal Qualitymentioning
confidence: 99%
“…Subsequently, Wakayama et al [43] investigated orthorhombic lysozyme crystallization in pseudo-microgravity utilizing the same magnet to simulate the microgravity environment in space. Nakamura et al [40] recently found that three of fifteen protein crystals showed a magnetic orientation and that the quality of five proteins was increased compared with those obtained in a magnetic field gradient using the same magnetic field.…”
Section: Magnet Systems That Provide a Strong And Stable Magnetic mentioning
confidence: 99%